Weed Management in Maize: Mulching is a Next Alternative to Herbicide - Timsina, Deepika; Sah, Shrawan Kumar; Adhikari, Pratishtha (Far Western Review, 2024)
Maize is the staple food crop of hills and a major component of livestock and poultry feed in Nepal. Controlling weeds is one of the most crucial elements that significantly impact maize production and profitability. Manual weeding is common but costly, whereas herbicidal weeding is effective but hazardous to the environment. In winter maize, broadleaf weeds are more dominant than grasses and sedges. (IVI), the highest IVI (Importance Value Index) was recorded in Poa annua L. (25%), and Ranunculus arvensis L. (24.2%) respectively. Weed infestation leads to yield losses ranging from 18% to as high as 85% depending on season and the intensity of weed infestation in crop fields. Depending upon the maize planting season, a critical period for weed control is 2 to 8 weeks in winter and 2 to 9 weeks in summer. Both live and plastic mulch reduces weed density and dry matter efficiently, blocks light to inhibit weed growth and also helps to conserve moisture and soil temperature. Weed control efficiency of black plastic mulch is highest at 96.2%, 90.10%, 85.62%, and 74.30% at 30 DAS, 60 DAS, 90 DAS, and at harvest respectively. In both Plastic and live mulch, yield attributes; such as ear harvested per hectare, number of grains per ear, and 1000 grains weight per cob are significantly affected which ultimately affects the yield. Overall, both live and plastic mulching techniques present sustainable alternatives to weed management contributing to the long-term viability of maize cultivation in Nepal.